Simulasi Antrian Retribusi BPHTB Menggunakan Metode Eksponensial - Mhd Ferdiansyah Putra; Rusmin Saragih; Anton Sihombing (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
Modern times now demand that everything must be fast and precise. This is because of the increasing population in the world today which continues to grow. Queue is an activity where customers wait to get service. Queue is a phenomenon that occurs in daily activities experienced by everyone. As a result of this queue many people turn to other places to avoid a queue and get maximum service. In the queuing system sometimes have problems, problems arise because of the many queues that are served. Long queues occur because of the many transactions at the cashier, both transfers, cash withdrawals, tax payments, and pension funds. The queuing model discussed in this study is a queue where customers come in groups. The number of customers in each group is a random variable, and the time between arrivals is an exponential distribution. In the research Exponential method is used to calculate the service time with a single channel to be able to observe how the system is performing.